2018
DOI: 10.1038/s42003-018-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

Facile carrier-assisted targeted mass spectrometric approach for proteomic analysis of low numbers of mammalian cells

Abstract: There is an unmet technical challenge for mass spectrometry (MS)-based proteomic analysis of single mammalian cells. Quantitative proteomic analysis of single cells has been previously achieved by antibody-based immunoassays but is limited by the availability of high-quality antibodies. Herein we report a facile targeted MS-based proteomics method, termed cPRISM-SRM (carrier-assisted high-pressure, high-resolution separations with intelligent selection and multiplexing coupled to selected reaction monitoring),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…Pairing the fluorescence-activated cell sorting (FACS) protocol with new methods for global proteome analysis of small numbers of cells (<200 cells) enabled us to compare the transcriptome and proteome for all six cell populations 27,28 (Supplementary Data #2). Despite the use of small cell numbers, particularly, for the rare EEC and tuft cell populations, we were able to quantify the expression of over 2,800 proteins and investigate RNA:protein correlation patterns ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Pairing the fluorescence-activated cell sorting (FACS) protocol with new methods for global proteome analysis of small numbers of cells (<200 cells) enabled us to compare the transcriptome and proteome for all six cell populations 27,28 (Supplementary Data #2). Despite the use of small cell numbers, particularly, for the rare EEC and tuft cell populations, we were able to quantify the expression of over 2,800 proteins and investigate RNA:protein correlation patterns ( Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that the addition of exogenous carrier proteins allows small numbers of mammalian cells to be effectively processed using conventional sample preparation protocols with minimal sample loss. 41 However, our previous approach required high-resolution PRISM to reduce the increased sample dynamic concentration range resulting from the addition of large amounts of carrier protein, thus generating many fraction samples that significantly lowered sample throughput. To alleviate this problem, we have developed a carrier-assisted LC–SRM approach for precise multiplexed analysis of small numbers of mammalian cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have recently developed a facile targeted mass spectrometric approach, termed cPRISM-SRM (carrier-assisted high-pressure, high-resolution separations with intelligent selection and multiplexing coupled to selected reaction monitoring), for enabling proteomic analysis of low numbers of cells. 41 For cPRISM-SRM, we used bovine serum albumin (BSA) (~50 μ g) as a carrier to minimize losses in conjunction with highly sensitive PRISM-SRM and found that we could detect low-abundance proteins in as few as 100 mammalian cells as well as high- to moderate-abundance proteins in single mammalian cell equivalents. This is ~3–4 orders of magnitude lower than the cell number required for current targeted MS methods (typically ~10 5 –10 6 cells).…”
mentioning
confidence: 99%
“…The many benefits of targeted MS-based assays described above (precision, harmonization, multiplexing, specificity) need to be weighed against the limitations of this platform. For example, while coupling immuno-affinity enrichment of peptides to targeted MS provides enhanced sensitivity for detection of proteins in clinical samples, the sensitivity of immuno-MS assays is currently not sufficient to support single cell analyses, although progress is being made towards this goal 125,126 . Unlike single cell techniques (e.g., immunohistochemistry, flow cytometry), MS-based assays quantify the average amount of peptides and proteins across thousands of cells, similar to other extraction-based techniques such as ELISA and Western blotting.…”
Section: Limitations Of Targeted Mass Spectrometry-based Assaysmentioning
confidence: 99%